2018
DOI: 10.1161/circinterventions.117.006368
|View full text |Cite
|
Sign up to set email alerts
|

Six-Year Follow-Up of Fractional Flow Reserve-Guided Versus Angiography-Guided Coronary Artery Bypass Graft Surgery

Abstract: FFR-guided CABG is associated with a significant reduction in the rate of overall death or myocardial infarction at 6-year follow-up as compared with angiography-guided CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 17 publications
4
89
0
4
Order By: Relevance
“…In a subgroup of 155 patients (25%) who underwent repeated coronary angiography for clinical indications, freedom from graft occlusion was higher in the FFR-guided group (21% in angiography-guided group, 5% in FFR-guided group, P = 0.031). The extended 6-year results were recently reported by Fournier and colleagues [34] and included 627 consecutive patients between 2006 and 2010. Both the rate of composite death or myocardial infarction (16% for FFR-guided group, 25% for angiography-guided group, P = 0.020) as well as death alone (11% for FFR-guided group, 18% for angiography-guided group, P = 0.013) were significantly lower in the FFR-guided CABG group.…”
Section: The Evolution Of Ffr In Coronary Artery Bypass Graftingmentioning
confidence: 91%
“…In a subgroup of 155 patients (25%) who underwent repeated coronary angiography for clinical indications, freedom from graft occlusion was higher in the FFR-guided group (21% in angiography-guided group, 5% in FFR-guided group, P = 0.031). The extended 6-year results were recently reported by Fournier and colleagues [34] and included 627 consecutive patients between 2006 and 2010. Both the rate of composite death or myocardial infarction (16% for FFR-guided group, 25% for angiography-guided group, P = 0.020) as well as death alone (11% for FFR-guided group, 18% for angiography-guided group, P = 0.013) were significantly lower in the FFR-guided CABG group.…”
Section: The Evolution Of Ffr In Coronary Artery Bypass Graftingmentioning
confidence: 91%
“…As shown in the DEFER trial (Deferral vs Performance of Percutaneous Coronary Intervention of Functionally FFR-Guided CABG Outcomes Non-Significant Coronary Stenosis) and FAME study (Fractional Flow Reserve Versus Angiography for Guiding Percutaneous Coronary Intervention), 11,12 Fournier et al 10 demonstrated that revascularization of ischemic lesions while deferring bypass on those without ischemia produces superior clinical results. Although surgeons and interventional cardiologists alike are predisposed to think that their revascularization procedures are purely beneficial or protective, the evidence suggests otherwise.…”
Section: See Article By Fournier Et Almentioning
confidence: 99%
“…With this in mind, in this issue of Circulation: Cardiovascular Interventions, Fournier et al 10 now report the extended 6-year results of their initial study 9 in which arteries were grafted based on either the angiographic severity or an FFR ≤0.80. Outcomes in 627 consecutive patients between 2006 and 2010 were analyzed by group; 198 having an FFR-guided approach on at least 1 artery and 429 having the standard angiographicguided approach.…”
Section: See Article By Fournier Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…SYNTAX 3 Revolution Study thus provides evidence base and a window of opportunity for incorporating the radiologist in the Heart-Team. The surgeon may thus serendipitously find an ally in the Heart-Team.The concept of physiological guidance to myocardial revascularization is now extended to CABG too and has been validated with a lower rate of all-cause mortality or myocardial infarction (16% vs 25%, p − 0.02) [4]. The results of the ongoing Graft patency after FFR-guided Versus Angio-guided CABG (GRAFFITI) trial too are keenly awaited and are likely to add weightage to this recommendation.…”
mentioning
confidence: 99%